Insulin pathway related genes and risk of colorectal cancer: INSR promoter polymorphism shows a protective effect - Pechlivanis, Sonalli; Pardini, Barbara; Bermejo, Justo Lorenzo; Wagner, Kerstin; Naccarati, Alessio; Vodičková, Ludmila; Novotný, Jan; Hemminki, Kari; Vodička, Pavel; Försti, Asta (Endocrine-related cancer, 2007)
Western lifestyle leading to obesity and type 2 diabetes has been associated with increased risk of colorectal cancer (CRC). Diet and related factors may affect the risk by modifying plasma insulin levels. Thus, the inter-individual variation in insulin signaling may play a plausible role in the development of CRC. We hypothesized that functional polymorphisms in the insulin pathway genes INS, INSR, IGFBPI, insulin receptor substrate 1 (IRS1), and IRS2 may be associated with CRC. We studied the association of five single nucleotide polymorphisms (SNPs) with the risk of CRC using a hospital-based case-control design with 712 cases and 748 controls from the Czech Republic. The INSR A-603G promoter SNP, which is located within a known Sp1-binding site, was associated with the risk of CRC, with carriers of the G allele having a decreased risk (odds ratios (OR) 0.71, 95% confidence interval (CI) 0.54-0.93). Carrying the variant allele of the IRS1 Gly972Arg SNP further decreased the risk among the INSR-603G allele carriers (OR 0.28, 95% CI 0.11-0.70). SNPs in the INS, IGFBPI, and IRS2 genes did not affect the risk of CRC. In conclusion, genetic variation in the insulin signaling pathway genes may affect the risk of CRC.
Keywords: dospělí; kolorektální nádory; Insulin Receptor Substrate Proteins; Female; fosfoproteiny; Adult; ženské pohlaví; CD antigeny; jednonukleotidový polymorfismus; Colorectal Neoplasms; lidé; Phosphoproteins; Polymorphism, Single Nucleotide; proteiny insulinového receptorového substrátu; signální transdukce; genetická predispozice k nemoci; studie případů a kontrol; Aged, 80 and over; Carcinoma; Genetic Predisposition to Disease; karcinom; Insulin; Receptor, Insulin; Signal Transduction; Risk Factors; Antigens, CD; Male; Case-Control Studies; Aged; rizikové faktory; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; promotorové oblasti (genetika); receptor inzulinu; Promoter Regions, Genetic; inzulin; Middle Aged; Humans